Synthesis and properties of semiconductor solid solutions (inSb)₁₋x(CdTe)x - Venger, E.F.; Knorozok, L.M.; Melnichuk, L.Yu.; Melnichuk, O.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
We consider the growth technology and investigations of indium antimonide doped concurrently with acceptor (Сd) and donor (Те) impurities taken in equiatomic ratio. The optimal modes of single crystal synthesis and crystallization are determined. It is shown that, when doping the indium antimonide, its lattice parameter changes considerably. This leads to deformation of the electron energy spectrum, changes the bandgap and charge carrier effective mass and affects the optical and electrical properties of indium antimonide samples. As a result, such material becomes suitable for fabrication of IR photodetectors.